PATTERN AND PREVALENCE OF WORK-RELATED MUSCULOSKELETAL DISORDERS AND ITS ASSOCIATION WITH QUALITY OF SLEEP AMONG FOOD VENDORS IN OGBOMOSHO, NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Food vendors are at risk of musculoskeletal disorders due to the awkward postures they attain while cooking and serving the food. The pain that results from musculoskeletal disorders could impact their sleep.Objective: This study investigated the prevalence of work-related musculoskeletal disorders (WMSDs) on food vendors' sleep quality. Method: This cross-sectional study was conducted on food vendors in selected food outlets in Ogbomosho, Nigeria. Data was collected on participants’ socio-demographics, prevalence of work-related musculoskeletal disorders using the Nordic Musculoskeletal Questionnaire and quality of sleep using the Pittsburgh Sleep Quality Index. Descriptive statistics and Chi-square were used to analyze the data. The alpha level was set at p≤0.05.Result: There were 82 participants [19 males (23.2%) and 63 females (76.8%)]. The mean age was 31.5±9.592 years. The average number of weekly working hours for participants was 69.95±17.318 hours. The majority of the participants (83%) reported having pain in one or more parts of the body in the last 12 months, with the low back (53.7%) and knees (51.2%) reported as the most affected regions. There was a significant association between WMSDs and participants' sleep quality (p = 0.003). Also, there was a significant association between sleep quality and the number of participants' work hours (p = 0.025).Conclusion: The study revealed a high prevalence of WMSDs among food vendors in Ogbomosho which was significantly associated with quality of sleep. Hence, proper education and awareness programmes on WMSDs and their prevention should be done for food vendors.
Keywords: work-related; musculoskeletal disorders; food vendors; sleep quality